Strategi Penjualan Toko Makanan Halal dan Peran Komunitas Muslim Pada Masa Pandemi Covid-19 di Jepang - Saktiawan, Amar; Iskandar, Kurniawaty (KIRYOKU, 2025)
This study aims to examine the conditions and strategies of halal food sales and the role of Muslim community in Japan in sustainability of halal food stores during the Covid-19 pandemic. Granovetter's network theory is used in analysis of the role of Muslim community network in supporting local halal food stores to survive the Covid-19 pandemic. The use of qualitative methods was carried out by collecting data through literature studies and interviews with three halal food store owners in Gifu, Okayama, and Osaka. The results of this study indicate that there are different impacts on sales between halal food stores in Japan during the Covid-19 pandemic. Various strategies have been carried out by halal food stores to maintain sales or increase purchasing interest as an effort to survive the Covid-19 pandemic. The Muslim community in Japan has an important role in efforts to maintain the sustainability of halal stores during the Covid-19 pandemic. Although the relationship between Muslims from another countries in Japan is included in the weak ties, when faced with a pandemic, it can trigger a change in relationships into strong ties.